Modern Waqf Management Maximizes Asset Potential with a Controlled Risk Approach - Siti Nur Farida (ICO EDUSHA, 2024)
Waqf is a social financial instrument in Islam which has great potential to support economic development and community welfare. However, in its management, waqf assets often face various challenges, such as lack of professional management, financial risks, and low productivity. This research examines the concept of modern waqf management which utilizes a controlled risk approach to maximize the potential of waqf assets. Using literature study methods and qualitative analysis, this research highlights productive waqf management models in several countries with a balanced risk approach. The research results show that modern waqf management with a controlled risk approach can increase the productivity of waqf assets and strengthen the role of waqf in economic development. Professional management with appropriate risk management has been proven to make a significant contribution in expanding the social benefits of waqf assets. Keywords: Modern waqf, risk management, productive assets, Islamic economics